(untitled) (International Journal of Studies in Nursing, 2022)
Background: The number of cancer survivors continues to increase worldwide. Health-related quality of life (HRQoL) is important as a health-related outcome for cancer patients and cancer survivors. Patients with early-stage non-small cell lung cancer may face the stress of symptoms and treatment side effects. However, for survivors of this type of cancer, the impact of cancer or treatment-related stress perception, symptoms, and psychological distress on HRQoL remains to be explored. Purpose: To examine the impact of stress appraisal, symptoms distress, and psychological distress (anxiety and depression) on quality of life in early-stage lung cancer survivors. Method: A cross-sectional study design using convenience sampling. Early-stage non-small cell lung cancer patients who had completed treatment of lung cancer for at least one month were recruited after obtaining informed consent. Self-administered questionnaires were used to collect demographics and information on clinical characteristics, perceived stress, symptoms distress, psychological distress (anxiety and depression), and HRQoL. Multiple regression analysis was used to identify factors affecting HRQoL. Results: The study recruited 85 (30 male and 55 female) lung cancer survivors with mean age of 63.20 years old (SD= 9.01), 85.8 % of which were diagnosed with stage I non-small cell lung cancer. Mean time since diagnosis was 3.33 years (SD = 2.05). All participants underwent surgery. We found that 52.6% of the variance (F (4, 80) =24.28, p<.001) in HRQoL was explained by the variables of anxiety (β= -.34, t= -3.36, p=.001), depression (β= -.28, t= -3.21, p=.002), perceived stress (β= -.21, t= -2.30, p=.024), and symptom distress (β= -.13, t= -1.53, p=.13). Conclusion: Our results suggest that health professionals should pay more attention to the assessment of perceived stress, psychological distress, and symptom distress for promoting HRQoL and healthy functioning of non-small cell lung cancer survivors.